2021
DOI: 10.1039/d1ob01592c
|View full text |Cite
|
Sign up to set email alerts
|

Visible-light-promoted synthesis of secondary and tertiary thiocarbamates from thiosulfonates and N-substituted formamides

Abstract: A general visible-light-promoted metal-free synthesis of secondary and tertiary thiocarbamates starting from thiosulfonates and N-substituted formamides is developed. By employing rhodamine B as photocatalyst and tert-butyl hydroperoxide (TBHP) as oxidant,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…Unfortunately, S-alkyl benzenethiosulfonate and Se-phenyl benzenesulfonoselenoate were not suitable for this reaction (3i and 3j), which most likely resulted from the instability of an alkyl sulfenyl radical (3i) 14 and the extremely photosensitive character of selenosulfonates (3j). 7a Further evaluation of this reaction showed that S-(het)aryl benzenethiosulfonates with electron-donating or electron-withdrawing groups as well as S-benzyl benzenethiosulfonate also successfully reacted with N,N-dimethylpropionamide, giving the corresponding products 3k-q in moderate to good yields (Scheme 3).…”
Section: Organic and Biomolecular Chemistry Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, S-alkyl benzenethiosulfonate and Se-phenyl benzenesulfonoselenoate were not suitable for this reaction (3i and 3j), which most likely resulted from the instability of an alkyl sulfenyl radical (3i) 14 and the extremely photosensitive character of selenosulfonates (3j). 7a Further evaluation of this reaction showed that S-(het)aryl benzenethiosulfonates with electron-donating or electron-withdrawing groups as well as S-benzyl benzenethiosulfonate also successfully reacted with N,N-dimethylpropionamide, giving the corresponding products 3k-q in moderate to good yields (Scheme 3).…”
Section: Organic and Biomolecular Chemistry Communicationmentioning
confidence: 99%
“…Among them, K 2 CO 3 and Na 2 CO 3 provided better isolated yields of 3a (77% and 73%) than did strong bases (KOH and NaOH) and an organic base (NEt 3 ) (47-53% yields). Following that, various organic photocatalysts (methylene blue, rose bengal, eosin B and Na 2eosin Y) and oxidants (K 2 S 2 O 8 , TBPB, BPO and DTBP) were separately evaluated (entries 7-10 and [11][12][13][14]. The results showed that a satisfactory isolated yield of 3a was obtained (87%) with Na 2 -eosin Y as the photocatalyst and TBHP as the oxidant (entry 10).…”
mentioning
confidence: 99%
“…Mao, Zhang, and co-workers reported the thiolation of the C-H bond of DMF using di-tert-butyl peroxide and either 1,2-di-p-tolyldisulfane (Scheme 19(a 1 )) or arylsulfonyl hydrazides and aluminum chloride (Scheme 19(a 2 )) [65], while Bi, Feng, Geng, and coworkers recently used tert-butyl hydroperoxide and S-aryl arenethiosulfonates under visible-light irradiation (Scheme 19b) [66]. This last procedure is, however, ineffective for DMF thiolation with 1,2-di-p-phenyldisulfane [66]. According to the authors [65,66], these reactions involve the radical I 4 .…”
Section: Conme2 Fragmentmentioning
confidence: 99%
“…This last procedure is, however, ineffective for DMF thiolation with 1,2-di-p-phenyldisulfane [66]. According to the authors [65,66], these reactions involve the radical I 4 . Jia's team, in the course of the study of functionalization of styrenes with thiosulfonates and arylboronic acids in acetone/DMF, also proposed that S-methyl dimethylcarbamothioate isolated as a by-product was formed from the reaction of S-methyl 4-methylbenzenesulfonothioate with I 4 (Scheme 19c) [67].…”
Section: Conme2 Fragmentmentioning
confidence: 99%
See 1 more Smart Citation